How Do the Locking Screws Lock? A Micro-CT Study of 3.5-mm Locking Screw Mechanism - Kaczmarek, Jakub; Bartkowiak, Tomasz; Paczos, Piotr; Gapinski, Bartosz; Jader, Hanna; Unger, Martin (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective To quantify the amount of the screw head thread and the plate hole thread connection in two 3.5 mm locking plates: Locking Compression Plate (LCP) and Polyaxial Locking System (PLS).Materials and Methods A micro - CT scan of a screw head - plate hole connection was performed pre- and post destructive tests. Tests were performed on bone surrogates in a fracture gap model. The 3.5 LCP and 3.5 PLS plates, with 3 perpendicular screws per segment were used in a destructive static test. The 3.5 PLS plates with mono- and polyaxial screws were compared in a cyclic fatigue tests in two orthogonal directions. Pre - and post - test scan datasets were compared. Each dataset was converted into serial images depicting sections cut orthogonally to locking screw axis. The amount of engagement was detected through automated image postprocessing.Results The mean amount of the thread connection for the LCP was 28.85% before and 18.55% after destructive static test. The mean amount of the connection for the PLS was 16.20% before and 14.55% after destructive static test. When inserted monoaxially, the mean amount of the connection for the PLS screws was 14.4% before and 19.24% after destructive cyclic test. The mean amount of the connection for the polyaxial inserted PLS screws when loaded against plate thickness was 2.99% before and 2.08% after destructive cyclic test. The mean amount of the connection for the polyaxial inserted PLS screws when loaded against plate width was 3.36% before and 3.93% after destructive cyclic test. The 3D visualization of the thread connection showed that the initial interface points between screw head and plate hole are different for both LCP and PLS after the destructive testing. Depending on the type of applied force, there was either loss or increase of the contact.Clinical Relevance Micro-CT offers news possibilities in locking implant investigation. It might be helpful in better understanding the nature of locking mechanism and prediction of possible mode of failure in different systems.
Keywords: micro-ct; locking screw; locking plate; polyaxial; LCP